2004
DOI: 10.1111/j.0737-6782.2004.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Technology Reconsidered: A Critique and Research Agenda

Abstract: The popular work by Clayton Christensen and colleagues on disruptive technology serves as a springboard to examine five key issues concerning the effect of technological change on firms and industries. This article challenges and integrates current theory in this domain, and raises questions to initiate new work. The discussion is organized around the following themes: the definition of disruptive technology, the predictive use of the theory of technological disruption, explaining the success of incumbents, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
586
1
27

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 787 publications
(626 citation statements)
references
References 47 publications
(63 reference statements)
12
586
1
27
Order By: Relevance
“…Empirical research also suggests that resource allocation processes using strategic buckets to manage sustaining versus disruptive projects independently are more effective in allowing disruptive innovation to flourish (Chao & Kavadias, 2007;Hogan, 2005). Companies should allocate financial and human resources to identify new potential customers, construct relationships with these customers, and develop knowledge about them (Danneels, 2002(Danneels, , 2003(Danneels, , 2004, because it is the emerging segments that value disruptive innovations at the time of their introduction (Govindarajan, Kopalle, & Danneels, 2011).…”
Section: Enabling Potential Disruptive Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research also suggests that resource allocation processes using strategic buckets to manage sustaining versus disruptive projects independently are more effective in allowing disruptive innovation to flourish (Chao & Kavadias, 2007;Hogan, 2005). Companies should allocate financial and human resources to identify new potential customers, construct relationships with these customers, and develop knowledge about them (Danneels, 2002(Danneels, , 2003(Danneels, , 2004, because it is the emerging segments that value disruptive innovations at the time of their introduction (Govindarajan, Kopalle, & Danneels, 2011).…”
Section: Enabling Potential Disruptive Innovationmentioning
confidence: 99%
“…Disruptive innovation theory has long been studied in the innovation management literature (Abernathy & Clark, 1985;Adner, 2002Adner, , 2006Calia, Guerrini, & Moura, 2007;Christensen, 2006;Christensen & Bower, 1996;Christensen & Raynor, 2003;Danneels, 2004;Govindarajan & Kopalle, 2006;Hall, Matos, & Martin, 2014;Kassicieh, Kirchhoff, Walsh, & McWhorter, 2002;Linton, 2002Linton, , 2004Linton, , 2009). The concept goes back at least to the seminal work by Abernathy and Clark (1985), who suggested that disruptive innovations often destroyed the value of existing technical competencies.…”
Section: Introductionmentioning
confidence: 99%
“…Daneels wrote: "Disruptive technology can be thought of as a technology that changes the essence of competition among firms by transforming the performance metrics" [11]. Based on this explanation and the uncertainty topology of Walker, we would like to propose a more elaborate definition of disruptive trends.…”
Section: Properties Of Disruptive Trendsmentioning
confidence: 99%
“…We envision, by contrast, sustaining innovation, whereby existing markets evolve to allow competition between firms that create better value [26,27]. Billions of dollars have already been spent creating Fig.…”
Section: Sustaining Innovationmentioning
confidence: 99%